Vergence eye movements impairments in schizophrenia and bipolar disorder. (December 2022) - Chrobak, Adrian Andrzej; Rybakowski, Janusz Kazimierz; Abramowicz, Maria; Perdziak, Maciej; Gryncewicz, Wojciech; Dziuda, Sebastian; Fafrowicz, Magdalena; Czarnecki, Paweł; Soltys, Zbigniew; Ceglarek, Anna; Ober, Jan Krzysztof; Marek, Tadeusz; et al.
Abstract: One of the most evaluated eye tracking tasks in schizophrenia (SZ) and bipolar disorder (BD) are smooth pursuit eye movements. They rely on the maintenance of slowly moving object on the fovea. While most of the studies evaluated tracking of a target that moves in the fronto-parallel plane, only two assessed vergence eye movements (VEM), which relies on the pursuit of object that moves in depth. The aim of our study was to compare VEM performance in SZ and BD. We evaluated 28 SZ patients, 32 BD patients and 25 healthy controls (HC). Participants underwent thorough optometric examination before eye tracking task. VEM were measured with the use of infrared eye tracker and dedicated vergence stimuli generator. SZ patients showed higher mean break and recovery points of fusion and shorter correct tracking time than HC. BD individuals revealed tracking accuracy deficits and higher number of saccades than HC. Compared to BD, SZ patients showed decrease of maximal convergence and divergence. Moreover, they presented tracking accuracy deficits of non-dominant eye: altered eyes positioning error during convergence and divergence gain. Exploratory analysis revealed significant gender differences between groups in terms of binocular VEM parameters. In this study we have recognized pattern of eye movement disturbances differentiating abovementioned groups. SZ patients showed decreased vergence tracking range with shorter tracking time and impaired accuracy of non-dominant eye, while BD patients showed higher number of saccades with decreased tracking accuracy. Neuroimaging studies are necessary to identify neuronal underpinnings of VEM impairments in SZ and BD. Highlights: Schizophrenia patients show decreased vergence tracking range. Schizophrenia patients reveal tracking accuracy deficits of non-dominant eye. Bipolar patients show higher number of saccades and tracking accuracy deficits. Vergence eye movements deficits differentiate patients' groups and healthy controls. Male schizophrenia patients present more severe eye movement deficits.